Cultural adaptation and validation of the mental illness associated stigma scale for Arabic-speaking population in Saudi Arabia - BinDhim, Nasser F.; Althumiri, Nora A.; Al-Luhaidan, Sulaiman M.; Alhajji, Mohammed; Saad, Sami Yahya A.; Alyami, Hussain; Svendrovski, Anton; Al-Duraihem, Rashed Abdullah; Alhabeeb, Abdulhameed Abdullah (Frontiers in Psychiatry, 2024)
Objective: This research aimed to culturally adapt and validate the MIAS scale for Arabicspeaking individuals within the Saudi Arabian general population, with an emphasis on cultural, societal, and individual nuances.Methods: An initial pilot testing with a small group ensured the scale's clarity. Subsequently, two cross-sectional studies involving 189 participants to assess structural validity of the Arabic MIAS scale, and 38 participants to assess the test-retest reliability. Descriptive statistics, Cronbach's α, Intraclass Correlation Coefficient (ICC), and Confirmatory Factor Analysis (CFA) were employed for data analysis.The Arabic MIAS scale demonstrated good internal consistency and acceptable test-retest reliability (ICC α=0.631). A three-factor model emerged (CFI = 0.890, TLI = 0.845, RMSEA = 0.094), including 'Outcomes,' 'Negative Stereotypes,' and 'Recovery,' closely mirroring the original study's structure. one item was excluded from the model since it didn't align with any of the three factors.The study contributes a culturally adapted, validated, non-condition-specific tool to gauge public attitudes towards mental health stigma in an Arabic context. It highlights the need for culturally sensitive stigma research and interventions and underscores the importance of improving such tools for cross-cultural applicability and comparability.